Luxury and sustainability: a common future? The match depends on how consumers define luxury. (2015) - Kapferer, Jean-Noël; Michaut, Anne
Sustainability issues have become a challenge for the luxury sector whose continuous success and growth - despite recessions, economic crises and increasing social inequality - appear as a paradox or even a provocation for some critics. Based on a program of multiple surveys involving actual luxury customers, we explain why customers are not concerned about sustainability considerations when they purchase a luxury product. But this apparent uninvolvement hides a more complex reality with high latent expectations towards luxury brands. Fundamentally, the perceived contradiction between luxury and sustainability depends on how luxury is defined by consumers: it is lower for consumers defining luxury in terms of exceptional quality. This is crucial for the defence of the legitimacy of the luxury sector as a whole, and of its most iconic brands for the future.